Efficacy of Endocardial Ablation of Drug-Resistant Ventricular Fibrillation in Brugada Syndrome: Long-Term Outcome. (August 2018) - Talib, Ahmed Karim; Takagi, Masahiko; Shimane, Akira; Nakano, Makoto; Hayashi, Tatsuya; Okajima, Katsunori; Kentaro, Minami; Fukada, Koji; Kowase, Shinya; Kurosaki, Kenji; Nitta, Junichi; Nishizaki, Mitsushiro; et al.
Abstract : Background: Both endocardial trigger elimination and epicardial substrate modification are effective in treating ventricular fibrillation (VF) in Brugada syndrome. However, the primary approach and the characteristics of patients who respond to endocardial ablation remain unknown. Methods: Among 123 symptomatic Brugada syndrome patients (VF, 63%; syncope, 37%), ablation was performed in 21 VF/electrical storm patients, the majority of whom were resistant to antiarrhythmic drugs. Results: Careful endocardial mapping revealed that 81% of the patients had no specific findings, whereas 19% of the patients, who experienced the most frequent VF episodes with notching of the QRS in lead V1, had delayed low-voltage fractionated endocardial electrograms. Ablation of VF triggers followed by endocardial substrate modification was performed in the right ventricular outflow tract in 85% of the cases and in the right ventricle in 15%. VF triggers could not be completely eliminated in 1 patient and VF became noninducible in 14 (88%) patients among 16 patients who underwent VF induction with normalization of Brugada-type ECG in 3. During follow-up (56.14±36.95 months), VF recurrence was observed in 7 patients. Importantly, all patients who had nothing of QRS in lead V1 did not respond to endocardial ablation despite presence of VF-triggering ectopic beats during ablation. Conclusions: With careful documentation of VF-triggering ectopic beats and detailed endocardial mapping, endocardial VF trigger elimination followed by endocardial substrate modification has an excellent long-term outcome, whereas presence of QRS notching in lead V1 was associated with high VF recurrence suggesting epicardial substrate ablation as effective initial approach.